Semiótica e Pragmatismo Interfaces Teóricas - Vol. II - Ibri, Ivo Assad (Editora Oficina Universitária, 2021)
Without losing rigor and thanks to his deep knowledge of this philosopher, Ivo Ibri makes Peirce accessible. [...] this work is of interest to both specialists in Peirce and those who seek a necessary approximation to the thought of a philosopher whom it is difficult to approach without a guide that leads us rigorously, but in an accessible way. [...] But Ivo Ibri is not only a Peirce Scholar, which would be a lot, but also a thinker whose ideas often take Peirce as a starting point for the development of his own thought, matured by his reflections and dialogues over the years. over several decades." Danilo Marcondes (PUC-RJ)